Soluble LRIG2 Ectodomain Is Released from Glioblastoma Cells and Promotes the Proliferation and Inhibits the Apoptosis of Glioblastoma Cells In Vitro and In Vivo in a Similar Manner to the Full-Length LRIG2 - Xiao, Qungen; Tan, Yihu; Guo, Yang; Yang, Hongkuan; Mao, Feng; Xie, Ruifan; Wang, Baofeng; Lei, Ting; Guo, Dongsheng (PLOS ONE, 2014)
The human leucine-rich repeats and immunoglobulin-like domains (LRIG) gene family contains LRIG1, 2 and 3, encoding integral membrane proteins with an ectodomain, a transmembrane domain and a cytoplasmic tail. LRIG1 negatively regulates multiple receptor tyrosine kinases signaling including the epidermal growth factor receptor (EGFR) and is a proposed tumor suppressor. The soluble LRIG1 ectodomain is demonstrated to be shed naturally and inhibit the progression of glioma. However, little is known regarding the functions of LRIG2. In oligodendroglioma, LRIG2 expression is associated with poor survival, suggesting that LRIG2 might have different functions compared with LRIG1. Since soluble LRIG1 ectodomain has a similar function to the full-length LRIG1, we hypothesize that the different roles exerted by LRIG2 and LRIG1 result from the difference of their ectodomains. Here, we addressed the functions of LRIG2 and LRIG2 ectodomain in the proliferation and apoptosis of glioma and the possible underlying mechanisms. Firstly, we found that LRIG2 expression levels positively correlated with the grade of glioma. Further, we demonstrated for the first time that soluble LRIG2 ectodomain was capable of being released from glioblastoma cells and exerted a pro-proliferative effect. Overexpression of LRIG2 ectodomain promoted the proliferation and inhibited the apoptosis of glioblastoma cells in vitro and in vivo in a similar manner to the full-length LRIG2. Both full-length LRIG2 and LRIG2 ectodomain were found to physically interact with EGFR, enhance the activation of EGFR and its downstream PI3 K/Akt pathway. To our knowledge, this is the first report demonstrating that soluble LRIG2 ectodomain is capable of being released from glioblastoma cells and exerts a similar role to the full-length LRIG2 in the regulation of EGFR signaling in the progression of glioblastoma. LRIG2 ectodomain, with potent pro-tumor effects, holds promise for providing a new therapeutic target for the treatment of glioblastoma.